Lung cancer risk in relation to indicative radon atlas metrics in Northern Ireland: a population-based case–control study using secondary data - Claire M. Delargy; Helen G. Coleman; Quentin G. Crowley; Damien Bennett; Javier Elio; Deirdre Fitzpatrick; Helen Mitchell; Sara M. Wallace; Rawan A. N. Alhattab; Angela Scott; Bernadette McGuinness; Ruth F. Hunter; et al. (Environmental Geochemistry and Health, 2026)
Radon is an established lung carcinogen, but more research is needed to inform whether area-based measures of radon exposure reflect underlying cancer risk. This study, the first of its kind in the UK, aimed to investigate the association between a nationwide indicative radon atlas and lung cancer risk in Northern Ireland, a region in which lung cancer screening programmes are under design. A population-based case–control study was conducted. Primary lung cancer cases ( n = 1,687) from the Northern Ireland Cancer Registry diagnosed in 2006 and 2014 were compared with 8,094 non-lung cancer controls from a large cohort. Radon exposure data were extracted from the Indicative Atlas of Radon, which categorises 1 km 2 areas by the percentage of households exceeding 200 Bq/m 3 . Exposure data were linked to participants by postcode. Logistic regression models adjusted for age, sex, smoking status, deprivation and PM 2.5 exposure were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for lung cancer. Individuals residing in high radon exposure areas (Atlas Class 6) had a greater than two-fold lung cancer risk (adjusted OR: 2.24, 95% CI: 1.25, 3.92) compared to residents in all other areas. This association was revealed after adjusting for PM 2.5 . This study supports the utility of an indicative radon atlas in reflecting underlying population lung cancer risk associated with radon, while highlighting constraints inherent to atlas-based exposure classification and secondary data.

Do some tiger sharks prefer beaches? Insights for shark management from a broad-scale comparative tracking study - Matthew N. McMillan; Adam Barnett; Stacy L. Bierwagen; Tracey B. Scott-Holland; Vinay Udyawer; Matthew Campbell; Richard Fitzpatrick; Nicolas Lubitz; Ingo B. Miller; Leanne M. Currey-Randall (Ocean & Coastal Management, 2026)

Species identification of modern and archaeological shark and ray skeletal tissues using collagen peptide mass fingerprinting - Michael Buckley; Ellie-May Oldfield; Cristina Oliveira; Clara Boulanger; Andrew C. Kitchener; Nicole R. Fuller; Traci Ardren; Victor D. Thompson; Scott M. Fitzpatrick; Michelle J. LeFebvre (Frontiers in Marine Science, 2024)
Introduction Elasmobranchs, such as sharks and rays, are among the world’s most endangered vertebrates, with over 70% loss in abundance over the past 50 years due to human impacts. Zooarchaeological baselines of elasmobranch diversity, distribution, and exploitation hold great promise for contributing essential historical contexts in the assessment of contemporary patterns in their taxonomic diversity and vulnerability to human-caused extinction. Yet, the historical ecology of elasmobranchs receives relatively less archaeological attention compared to that of ray-finned fishes or marine mammals, largely due to issues of taxonomic resolution across zooarchaeological identifications. Methods We explore the use of Zooarchaeology by Mass Spectrometry (ZooMS) for species identification in this unstudied group, using an archaeological case study from the marine environments of the Florida Keys, a marine biodiversity hotspot that is home to an array of elasmobranch species and conservation efforts. By comparison with 39 modern reference species, we could distinguish 12 taxa within the zooarchaeological assemblage from the Clupper archaeological site (Upper Matecumbe Key) that included nine sharks, two rays and a sawfish. Results and discussion The results indicate that, through additional complexity of the collagen peptide mass fingerprint, obtained due to the presence of the cartilaginous type II collagen, ZooMS collagen peptide mass fingerprinting provides exceptionally high taxonomic resolution in this group, yielding species-level identifications in all cases where sufficient reference material was used. This case study also highlights the added value of ZooMS for taxa that are more difficult to distinguish in zooarchaeological analyses, such as vertebrae of the Atlantic sharpnose shark ( Rhizoprionodon terraenovae ) and the hammerhead sharks ( Sphyrna spp.) in the Florida Keys. Therefore, the application of collagen peptide mass fingerprinting to elasmobranchs offers great potential to improve our understanding of their archaeological past and historical ecology.

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

The structure and organisation of an Amazonian bird community remains little changed after nearly four decades in Manu National Park - Ari E. Martínez; José M. Ponciano; Juan P. Gomez; Thomas Valqui; Jorge Novoa; Mariamercedes Antezana; Gabriela Biscarra; Ettore Camerlenghi; Blaine H. Carnes; Renato Huayanca Munarriz; Eliseo Parra; Isabella M. Plummer; et al. (Ecology Letters, 2023)
Documenting patterns of spatiotemporal change in hyper‐diverse communities remains a challenge for tropical ecology yet is increasingly urgent as some long‐term studies have shown major declines in bird communities in undisturbed sites. In 1982, Terborgh et al. quantified the structure and organisation of the bird community in a 97‐ha. plot in southeastern Peru. We revisited the same plot in 2018 using the same methodologies as the original study to evaluate community‐wide changes. Contrary to longitudinal studies of other neotropical bird communities (Tiputini, Manaus, and Panama), we found little change in community structure and organisation, with increases in 5, decreases in 2 and no change in 7 foraging guilds. This apparent stability suggests that large forest reserves such as the Manu National Park, possibly due to regional topographical influences on precipitation, still provide the conditions for establishing refugia from at least some of the effects of global change on bird communities.

Advancing Social Equity in and Through Marine Conservation - Nathan J. Bennett; Laure Katz; Whitney Yadao-Evans; Gabby N. Ahmadia; Scott Atkinson; Natalie C. Ban; Neil M. Dawson; Asha de Vos; Juno Fitzpatrick; David Gill; Mael Imirizaldu; Naia Lewis; et al. (Frontiers in Marine Science, 2021)
Substantial efforts and investments are being made to increase the scale and improve the effectiveness of marine conservation globally. Though it is mandated by international law and central to conservation policy, less attention has been given to how to operationalize social equity in and through the pursuit of marine conservation. In this article, we aim to bring greater attention to this topic through reviewing how social equity can be better integrated in marine conservation policy and practice. Advancing social equity in marine conservation requires directing attention to: recognition through acknowledgment and respect for diverse peoples and perspectives; fair distribution of impacts through maximizing benefits and minimizing burdens; procedures through fostering participation in decision-making and good governance; management through championing and supporting local involvement and leadership; the environment through ensuring the efficacy of conservation actions and adequacy of management to ensure benefits to nature and people; and the structural barriers to and institutional roots of inequity in conservation. We then discuss the role of various conservation organizations in advancing social equity in marine conservation and identify the capacities these organizations need to build. We urge the marine conservation community, including governments, non-governmental organizations and donors, to commit to the pursuit of socially equitable conservation.

Initial evaluations of a Gulf of Mexico/Caribbean ocean forecast system in the context of the Deepwater Horizon disaster - Edward D. Zaron; Patrick J. Fitzpatrick; Scott L. Cross; John M. Harding; Frank L. Bub; Jerry D. Wiggert; Dong S. Ko; Yee Lau; Katharine Woodard; Christopher N. K. Mooers (Frontiers of Earth Science, 2015)

Intensified mollusk exploitation on Nevis (West Indies) reveals ~six centuries of sustainable exploitation - Aaron S. Poteate; Scott M. Fitzpatrick; Meagan Clark; Jessica H. Stone (Archaeological and Anthropological Sciences, 2015)

Isolation and characterization of eight polymorphic microsatellite loci for Natterer’s bat, Myotis nattereri (Vespertilionidae, Chiroptera) - David D. Scott; Seán Fitzpatrick; Deborah A. Bailie; Emma S. M. Boston; Mathieu G. Lundy; Daniel J. Buckley; Emma C. Teeling; W. Ian Montgomery; Paulo A. Prodöhl (Conservation Genetics Resources, 2013)

Archaeology and coastal conservation - Torben C. Rick; Scott M. Fitzpatrick (Journal of Coastal Conservation, 2012)

New records for prehistoric introduction of Neotropical mammals to the West Indies: evidence from Carriacou, Lesser Antilles - Christina M. Giovas; Michelle J. LeFebvre; Scott M. Fitzpatrick (Journal of Biogeography, 2012)
Aim This paper investigates the prehistoric introduction of five mammalian taxa to Carriacou (Lesser Antilles) and refines the known anthropogenic ranges for these fauna in the pre‐Columbian West Indies. The importance of such records for understanding the region’s historical biogeography and ecology is considered. Location Carriacou Island, Grenada (12°28′ N, 61°26′ W). Methods Zooarchaeological assemblages from Carriacou’s earliest documented prehistoric sites, Grand Bay and Sabazan, were analysed, and exotic taxa were identified and quantified. The timing of introductions was established based on multiple radiocarbon assays, including three new accelerator mass spectrometry (AMS) direct dates obtained on the bone of exotic taxa. Source species and location(s) are considered and compared with known prehistoric records for the Caribbean to synthesize anthropogenic distributions for the pre‐Columbian period. The contexts of the zooarchaeological remains are evaluated to better understand the nature and purpose of introductions. Results Zooarchaeological investigation on Carriacou reveals the occurrence of multiple mammal introductions from South American between c . ad 700 and ad 1400. This paper presents the first records for guinea pig ( Cavia sp.), armadillo ( Dasypus sp.), peccary ( Tayassu/Pecari sp.), opossum ( Didelphis sp.) and agouti ( Dasyprocta sp.) from the island. Human‐mediated transport of these taxa is indicated by their absence from the record prior to human settlement of Carriacou. Several translocated species are either rare or entirely unknown for the region, and overall West Indian distributions are temporally and spatially discontinuous. Archaeological contexts indicate that mammalian introductions arose from human subsistence needs, but other social factors may have shaped the dispersal of these fauna. Main conclusions The taxonomic combination and richness of Carriacou’s introduced fauna are unusual within the region. Importantly, the new records significantly improve the known pre‐Columbian geographic range for peccary, guinea pig and armadillo. Integrated with regional records, these data augment our understanding of the Caribbean’s historical biogeography, and have the potential to improve our understanding of human mobility and anthropogenic environmental impacts in the West Indies prior to the arrival of Europeans.